Evaluasi Kinerja BUMD Kabupaten Purbalingga - Suroso, Agus (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
The objective of this research is to measure the significant of Municipal Enterprises (BUMD) performance. This research is very important for BUMDmanagement and executive committe of Purbalingga Regency for self-evaluation. Higher performance beside will give the more original income (PAD), it will fullfill theaccountability and transparency of public sector. Population of the research is whole of the BUMD in Purbalingga Regency. Wenuse the judgement method to obtain sampel. Base on that method, we took 3 BUMD, they are PDAM, Apotik Purbahusada and Purbalingga Ventura. The unaudited financial statement as data for measure the performance ratios are Return On Equity (ROE), Return on Investment (ROI), Profitabilty Ratios, and Likuidity Ratios. Result of the research show that the performance of BUMD based on the four indicators ratios have increased.